Management of overactive bladder. Issue 1 (January 2020) - Basu, Maya
Abstract: Overactive bladder is a common and bothersome condition which has a major and measurable impact on sufferers' quality of life. The cardinal symptom of urgency, with or without urgency incontinence, frequency and nocturia is thought to be caused by abnormalities in detrusor smooth muscle function and/or sensory pathways. A structured assessment approach is of importance, including a detailed history of symptoms, medical and drug history and lifestyle factors such as fluid intake. Conservative management revolves around the key principles of fluid modification, avoidance of potential triggers and bladder retraining. Pharmacological options include antimuscarinic and beta agonist drugs. These medications have proven efficacy but compliance varies due to side effects and poor tolerability. Anti-cholinergic burden is an important factor to consider in prescribing to older women taking concurrent medications. If conservative and medical therapy is ineffective, further options include intra-detrusor botulinum toxin injections and neuromodulation.